Restriction endonuclease analysis of mitochondrial DNA from grande and genetically characterized cytoplasmic petite clones of Saccharomyces cerevisiae. - Morimoto, R (1975)
Digestion of grande mitochondrial DNA (mtDNA) BY EcoRI restriction endonuclease gives rise to nine fragments with a total molecular weight of 51.8 x 10(6). HindIII digestion yields six fragments with a similar total molecular weight. Specific restriction fragments can be detected despite the fact that yeast mtDNA consists of a heterogeneous distribution of randomly broken molecules. Digestion patterns of 10 genetically characterized petite clones containing various combinations of five antiobiotic resistance markers indicate that the petite mtDNA predominantly represents deletion of the grande genome. The petite mtDNAs contained up to seven EcoRI restriction fragments which comigrate with grande restriction fragments, and at least one fragment that did not correspond to any in the grande. Some strains contained multiple fragments with mobility different from that of grande; these fragments were usually present in less than molar concentrations. The genetic markers were associated with individual sets of restriction fragments. However, several internal inconsistencies prevent the construction of a definitive genetic fragment map. These anomalies, together with the digestion patterns, provide strong evidence that, in addition to single contiguous deletion, other changes such as multiple deletion and heterogeneity of mtDNA populations are present in some of the petite mtDNAs.